2013
DOI: 10.1038/ajg.2013.91
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Cytokine Response After Short-Term Gluten Challenge in Celiac Disease and Non-Celiac Gluten Sensitivity

Abstract: CD patients mounted a concomitant innate and adaptive immune response to gluten challenge. NCGS patients had increased density of intraepithelial CD3(+) T cells before challenge compared with disease controls and increased IFN-γ mRNA after challenge. Our results warrant further search for the pathogenic mechanisms for NCGS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
125
1
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(146 citation statements)
references
References 45 publications
12
125
1
8
Order By: Relevance
“…In 2011, Sapone etal suggested an innate immune response [112] with activation of toll like receptors while other studies have suggested increased intestinal permeability to be responsible [113][114][115][116]. Increased CD3 positive IEL105,112-117 and increased interferon γ to a gluten challenge [117] suggests gut mucosal activation.…”
Section: Non-celiac Gluten Sensitivity (Ncgs)mentioning
confidence: 99%
“…In 2011, Sapone etal suggested an innate immune response [112] with activation of toll like receptors while other studies have suggested increased intestinal permeability to be responsible [113][114][115][116]. Increased CD3 positive IEL105,112-117 and increased interferon γ to a gluten challenge [117] suggests gut mucosal activation.…”
Section: Non-celiac Gluten Sensitivity (Ncgs)mentioning
confidence: 99%
“…Nevertheless, translation into human studies has shown varying pathology, immunology and conflicting mucosal immunological events. [27][28][29][30] Interpreting and drawing definitive conclusions from the few clinical trials that focus on NCGS is difficult because of weaknesses in the study design or execution, for example inconsistent definition of NCGS and inclusion criteria, small number of participants, inclusion of participants with elevated markers of coeliac disease (intraepithelial lymphocytosis in the duodenum and evidence of immunological activation), or the non-distinction between gluten and other wheat components.…”
Section: The Current Evidence For Ncgsmentioning
confidence: 99%
“…Recently, Brotveit et al [18] showed that NCGS patient had and increased density of intraepithelial CD3(?) T cells at baseline and a significant increase in interferon-c mRNA following gluten challenge suggesting that the adaptive immune system may play a role in NCGS.…”
Section: Pathogenesismentioning
confidence: 99%